Environmental Health Research in Africa: Important Progress and Promising Opportunities - Joubert, Bonnie R.; Mantooth, Stacey N.; McAllister, Kimberly A. (Frontiers in Genetics, 2020)
The World Health Organization in 2016 estimated that over 20% of the global disease burden and deaths were attributed to modifiable environmental factors. However, data clearly characterizing the impact of environmental exposures and health endpoints in African populations is limited. To describe recent progress and identify important research gaps, we reviewed literature on environmental health research in African populations over the last decade, as well as research incorporating both genomic and environmental factors. We queried PubMed for peer-reviewed research articles, reviews, or books examining environmental exposures and health outcomes in human populations in Africa. Searches utilized medical subheading (MeSH) terms for environmental exposure categories included in the March 2018 US National Report on Human Exposure to Environmental Chemicals, which includes chemicals with worldwide distributions. Our search strategy retrieved 547 relevant articles, with studies evaluating health impacts of ambient air pollution (n=108), indoor air pollution (n=164), heavy metals (n=132), pesticides (n=94), dietary mold (n=62), indoor mold (n=9), per- and polyfluoroalkyl substances (PFASs, n=0), electronic waste (n=9), environmental phenols (n=4), flame retardants (n=3), and phthalates (n=3), where articles could belong to more than one exposure category. Only 23 articles characterized both environmental and genomic risk factors. Cardiovascular and respiratory health endpoints impacted by air pollution were comparable to observations in other countries. Air pollution exposures unique to Africa and some other resource limited settings were dust and specific occupational exposures. Literature describing harmful health effects of metals, pesticides, and dietary mold represented a context unique to Africa. Studies of exposures to phthalates, PFASs, phenols, and flame retardants were very limited. Our review underscores the need for further focus on current and emerging environmental and chemical health risks as well as better integration of genomic and environmental factors in African research studies. Environmental exposures with distinct routes of exposure, unique co-exposures and co-morbidities, combined with the extensive genomic diversity in Africa may lead to the identification of novel mechanisms underlying complex disease and promising potential for translation to global public health.